PELATIHAN PENGOLAHAN LIMBAH KAIN PERCA MENJADI PRODUK AKSESORIS DESAIN INTERIOR DI BANK SAMPAH GULON ASRI, JEBRES, SURAKARTA - Alimin, Nurhayatu Nufut; Murni, Endri Sintiana; Cahyani, Dwi (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Basically, the cloth is indispensable in the interior design sector, especially in the manufacture of interior accessories products made from textiles or upholstery. The problem of fabric waste that is abundant and difficult to decompose should be a solution for interior design products. Interior Design can utilize patchwork waste into products that have beauty, function, and economic value. Therefore, this community service activity at the Gulon Asri Waste Bank focuses on processing patchwork into interior accessory products, such as blankets, carpets, pillows, and others. Then the product is packaged and marketed online.